SPECIFIC FEATURES OF THE EDUCATIONAL PROCESS IN PRESCHOOL EDUCATION ON THE BASIS OF DUAL EDUCATION (Journal of Universal Science Research, 2026)
The organization of the preschool educational process on the basis of dual education is of great importance in increasing the effectiveness of education. This system combines theoretical knowledge with practice, ensures the active participation of children and contributes to the development of their independent thinking and creative abilities.